PEMBEKALAN DOKTRIN SOTERIOLOGI DAN ANTROPOLOGI GUNA PEMBENTUKAN JATI DIRI SISWA KELAS VIII SMP KRISTEN YSKI, SEMARANG, JAWA TENGAH - Kristiawan, Ragil (Jurnal PKM Setiadharma, 2024)
Teenage life is a life of searching for one's identity. In these times, it is essential to be able to lay the foundations of Christianity in their lives so that teenagers do not make the wrong choices. Two fundamental doctrines teenagers need to know are Christian soteriology and Christian anthropology. Soteriology discusses how God's plan of salvation works in the lives of teenagers. Anthropology examines the self-image of teenagers whom the blood of Christ has redeemed. Understanding these two fundamental doctrines is very important in the lives of today's teenagers. Based on this need, SMP Kristen YSKI held Community Service activities as a Refreshing Course, which was held for class VIII SMP. This activity was carried out because class VIII students had never been provided with the fundamental doctrines of Christianity, especially those of soteriology and Biblical anthropology. This activity will be held on January 11-12, 2024, at Wisma Elika Bandungan, Central Java. The resource person used interactive lectures and question-and-answer methods to guide students. Students have received the necessary provision so that they understand this central doctrine of Christianity. In the end, a correct understanding of salvation and a Biblical self-image will determine their future steps in life by the teachings of the Bible.